The effects of an "ideal protein" lactation diet on sow and litter performance - Laurin, J.L.; Hansen, J.A.; Richards, R.D.; Huffman, C.E.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred lactating sows were used to determine the influence of an ideal protein lactation diet on sow productivity. Sows were fed either a 15.8% crude protein, corn soybean meal, control diet or a 12.6% protein diet supplemented with synthetic amino acids to a 15.8% crude protein equivalent. Lactation diet had no influence on litter weaning wt (114.5 vs 114.7 lb), daily feed intake (12.5 vs 12.7 lb), pig survivability (92.3 vs 93.1 %), or sow backfat loss (.11 vs .12 in). However, sows fed the ideal protein diet lost more weight than sows fed the control diet (18.6 vs 25.1 lb). These results indicate that an ideal protein diet based on synthetic amino acid additions can be effectively used during lactation without depressing sow milk production, as measured by litter weaning wt. However, the ideal protein diet did not improve sow productivity and resulted in increased sow weight loss.
Keywords: Swine; Sow; Performance; AA; Intake; Protein